ANALYSES OF CHARATER AND CHARACTERIZATION OF THE NOVEL “LOVE BENEATH THE WINGS” BY KEZIA NADIRA PUBLISHED ON 2013 - Agustinus Lia Masan; Lisa A.G. Loupatty; Vantri Pieter Kelelufna (Prodi Pendidikan Guru Sekolah Dasar (PGSD) FKIP Universitas Pattimura, 2020)
The research with the title of analysis character and characterization in the novel